2016
DOI: 10.1007/s11213-016-9375-6
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Interdisciplinary Cooperation on Computer and English: A Case Study of Aletheia University Participated in International Volunteer Service Learning to Inner Mongolia

Abstract: This action research encompasses both descriptive and prescriptive treatment of the process and outcomes of an international and interdisciplinary volunteer service learning project. The project was held in a Junior High School in Suniteyou, Xilingol League in Inner Mongolia. The descriptive, qualitative aspect captures the reflections and thoughts of volunteer-service students. Sample participants include two teachers and fourteen students (five from the department of English, and nine from Information Manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some studies have confirmed a positive effect of SL on student happiness in different social environments, for example, a SL intervention carried out by university students with adolescents with low resources in Mongolia (Shu-Chin and Tzong-Heng, 2016) or a SL intervention carried out by preservice teachers with minors with special educational needs in Spain (Capella-Peris et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Some studies have confirmed a positive effect of SL on student happiness in different social environments, for example, a SL intervention carried out by university students with adolescents with low resources in Mongolia (Shu-Chin and Tzong-Heng, 2016) or a SL intervention carried out by preservice teachers with minors with special educational needs in Spain (Capella-Peris et al, 2020).…”
Section: Introductionmentioning
confidence: 97%